How St. Augustine Could Love the God in Whom He Believed - Miles, Margaret R. (Augustinian studies, 2023)
St. Augustine, pictured by Western painters holding in his hand his heart blazing with passionate love, consistently and repeatedly insisted―from his earliest writings until close to his death―that the essential characteristic of God is "God is love" (1 John 4:16). Yet he also insisted on the doctrines of original sin and everlasting punishment for the massa damnata. This article will not explore the rationale or semantics of his arguments, nor the detail and nuance of the doctrines of predestination and perseverance. Rather, I seek to understand, from Augustine’s last writings, how he reconciled his strong conviction that God is love with doctrines requiring belief in a God who determined the fate of individuals to eternal reward or punishment "before the foundation of the world" (Eph. 1:4), a God indifferent to individuals’ actions, struggles, or longings. My primary interest is not on Augustine’s ability to render these two apparently opposing ideas of God intellectually compatible, but rather on his feeling, gathered from his last sermons, as he approached death. In brief, how could Augustine love the God in whom he believed?